Energy-absorbing performance of graded Voronoi foams. (November 2019) - Lin, Hui; Lv, Lin; Zhang, Jianjun; Wang, Zhihua
Cellular foams are usually used as energy absorbers in engineering such as cushioning to alleviate the impact energy. To explore their energy absorption property, Voronoi foams with different density gradients were established. Numerical simulations were conducted by using Ls-dyna 971. Two loading conditions were considered: the constant velocity impact and the densification velocity impact. The results indicate that the energy absorption is closely related to loading conditions and profiles of density gradients. Therefore, it is of great importance to select suitable graded foams accordingly. This study paves the way for engineering applications of graded cellular materials as protective devices.